1987
DOI: 10.3758/bf03208214
|View full text |Cite
|
Sign up to set email alerts
|

The interaction between stimulus variations and age trends in the Poggendorff illusion

Abstract: Variations in stimulus parameters (distance between the parallels and angle of the transversal) in the Poggendorff illusion were used to explore possible reasons for inconsistencies in the age trends in illusion magnitude found in earlier studies. The data show that the Poggendorff illusion is very sensitive to parametric manipulations and that the age trends are quite different for different configurations of the stimulus array. Systematic sex differences in illusion magnitude were also found.Although the mag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
5
1

Year Published

1987
1987
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 21 publications
1
5
1
Order By: Relevance
“…Inspection of all scores revealed that expansion targets with relatively long fins yielded higher coefficients. This result is consistent with the point made by Girgus and Coren (1987) that the role of organismic variables is best assessed by targets that induce large distortions. However, it appears that, at best, only about 5% to 10% of the variance is attributable to stable individual differences in attention deployment.…”
Section: Spatial Distribution Of Attention and Asymmetry In Distortionsupporting
confidence: 80%
“…Inspection of all scores revealed that expansion targets with relatively long fins yielded higher coefficients. This result is consistent with the point made by Girgus and Coren (1987) that the role of organismic variables is best assessed by targets that induce large distortions. However, it appears that, at best, only about 5% to 10% of the variance is attributable to stable individual differences in attention deployment.…”
Section: Spatial Distribution Of Attention and Asymmetry In Distortionsupporting
confidence: 80%
“…The present fmding of an absence of any age trend for Poggendorff misalignment or interior underestimation conflicts with results of previous work (Girgus & Coren, 1987;Leibowitz & Gwozdecki, 1967). Girgus and Coren's interpretation suggests that the dimensions of the illusion figures used in the present study may not have been sufficiently powerful to produce significant age trends.…”
contrasting
confidence: 83%
“…The Poggendorff illusion offers two different ways to assess illusion magnitude. One way is to measure the magnitude of apparent noncollinearity of the diagonal segments or transversals (see Girgus & Coren, 1987;Leibowitz & Gwozdecki, 1967). An alternative and perhaps more fundamental assessment technique requires subjects to judge the intertransversal extent.…”
mentioning
confidence: 99%
“…Because SQ is known to differ significantly between men and women (Baron-Cohen et al 2003), as is the susceptibility to some illusions (e.g., Girgus and Coren 1987; Philips et al 2004; Voyer et al 1995; but see also Porac et al 1979), it is important to determine whether the correlation between SQ and illusion susceptibility is merely driven by gender differences. This was accomplished with a linear regression that separately assessed the contributions of gender and SQ on susceptibility factor #1 mod , using ranked SQ and susceptibility scores for a nonparametric test.…”
Section: Resultsmentioning
confidence: 99%